A shared mechanism of muscle wasting in cancer and Huntington's disease. Issue 1 (14th December 2015) - Mielcarek, Michal; Isalan, Mark
Abstract: Skeletal muscle loss and dysfunction in aging and chronic diseases is one of the major causes of mortality in patients, and is relevant for a wide variety of diseases such as neurodegeneration and cancer. Muscle loss is accompanied by changes in gene expression and metabolism that lead to contractile impairment and likely affect whole‐body metabolism and function. The changes may be caused by inactivity, inflammation, age‐related factors or unbalanced nutrition. Although links with skeletal muscle loss have been found in diseases with disparate aetiologies, for example both in Huntington's disease (HD) and cancer cachexia, the outcome is a similar impairment and mortality. This short commentary aims to summarize recent achievements in the identification of common mechanisms leading to the skeletal muscle wasting syndrome seen in diseases as different as cancer and HD. The latter is the most common hereditary neurodegenerative disorder and muscle wasting is an important component of its pathology. In addition, possible therapeutic strategies for anti‐cachectic treatment will be also discussed in the light of their translation into possible therapeutic approaches for HD.